2011
DOI: 10.1136/jmedgenet-2011-100133
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diagnosis of Duchenne and Becker muscular dystrophy using next-generation sequencing technology: comprehensive mutational search in a single platform

Abstract: Background Duchenne muscular dystrophy or Becker muscular dystrophy might be a suitable candidate disease for application of next-generation sequencing in the genetic diagnosis because the complex mutational spectrum and the large size of the dystrophin gene require two or more analytical methods and have a high cost. The authors tested whether large deletions/ duplications or small mutations, such as point mutations or short insertions/deletions of the dystrophin gene, could be predicted accurately in a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 30 publications
3
66
0
Order By: Relevance
“…19 Recent studies applying NGS have proven its ability in detecting SNVs and large deletions/ duplications in the dystrophin gene in males. 15,20 However, the detection of CNV in female carriers by targeted NGS approaches had not been reported to date. Compared with haploid X chromosomes in male, the CNV detection in females with diploid X chromosomes would be more complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Recent studies applying NGS have proven its ability in detecting SNVs and large deletions/ duplications in the dystrophin gene in males. 15,20 However, the detection of CNV in female carriers by targeted NGS approaches had not been reported to date. Compared with haploid X chromosomes in male, the CNV detection in females with diploid X chromosomes would be more complex.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Lim et al 15 reported a mutational search platform for the genetic diagnosis of DMD/BMD, but only a small number of samples was included; these authors only reported the detection of large deletion/duplication mutations in male patients. In the present study, we developed a novel computational framework and applied this platform to identify copy number variations (CNVs) and single-nucleotide variations (SNVs) in a large cohort at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…The DMD gene may be sequenced as part of an in-house gene panel, a commercially available sequencing gene panel such as TruSight One (Illumina), or a whole exome. Single-step methods able to detect exon copy variants and exonic point variants are also streamlining this process [23][24][25][26]. Point variants affecting splicing (including those deep within intronic regions of DMD) can affect RNA expression and/or processing.…”
Section: Methodsmentioning
confidence: 99%
“…MLPA has an analytical sensitivity of~71% and when combined with Sanger or massively parallel sequencing of the coding regions and splice sites following negative MLPA results, the analytical sensitivity becomes~97% [29]. Some mutational analyses using single platforms have achieved sensitivities from 92 to 99% [23,25,26]. Array CGH can identify complex rearrangements that go undetected by MLPA [36].…”
Section: Analytical Sensitivitymentioning
confidence: 99%
“…Lim et al 13 reported a mutational search platform for the genetic diagnosis of DMD/BMD. Wei et al 14 also reported a mutational search for DMD/BMD and female carriers using targeted NGS on HiSeq2000 (Illumina, San Diego, CA, USA).…”
Section: Introductionmentioning
confidence: 99%